FALSE HALAL LABELING IN PORK-CONTAMINATED PRODUCT: A QUALITATIF STUDY OF CONSUMER TRUST IN MADURA, INDONESIA - Deviana Putri Septia Ningrum; Firman Setiawan; Trischa Relanda Putra; Dianna Suzienna Mohammad Shah (Ekonomi Islam, 2026)
Research aims: This study analyzes the impact of false halal labeling on pork-contaminated products on Muslim consumer trust in Madura, Indonesia, and identifies factors influencing community perceptions and responses to such practices. Design/Methodology/Approach: This study employs a qualitative descriptive-analytical approach. Data were collected through in-depth interviews and non-participant observation involving Muslim consumers across four regencies in Madura. Thematic analysis using NVivo 12 Plus was applied, with validity ensured through triangulation and member checks. Research findings: The study identifies four main themes: consumer trust in halal labeling, perceptions of certification agencies and government performance, and impacts on consumer behavior. Findings reveal a shift from unquestioning acceptance toward more cautious and selective attitudes. Consumers increasingly verify ingredients, halal registration numbers, and manufacturer reputations. Fraud cases have weakened trust in both products and certification institutions, with concerns over weak supervision, low transparency, and limited public education. Consumers also experience anxiety, betrayal, and religious concern, viewing violations as breaches of religious values. Theoretical Contribution/Originality: This study extends consumer behavior theory by showing how halal labels function as religious symbols, safety guarantees, and institutional credibility markers. Practical/Policy Implications: Stronger monitoring, transparent certification processes, digital traceability, and consumer education are needed to restore trust, supported by stricter enforcement and collaboration among stakeholders. Research Limitations/Implications: Limited to Madura; broader studies are needed for generalization. Keywords: False halal labeling; consumer trust; pork contamination; halal certification; Muslim consumers; Madura.